Gestión de la jefatura de compras públicas y su relación con la administración de contratos del gobierno autónomo descentralizado municipal del cantón Mocache periodo 2019-2022 - Macías Cedeño, Cinthia Janine (2023)
The Public Procurement Office of the Autonomous Decentralised Municipal Government of Mocache canton has experienced deficiencies in its management and non-compliance with public procurement regulations, according to report DPLR-0009-2022 of the Comptroller General of the State. The aim of this research was to evaluate the management of the Head of Public Procurement and its relationship with the Contract Administration of the Autonomous Decentralised Municipal Government of Mocache Canton in the period 2019-2022. Field, documentary and descriptive types of research were used, with inductive and deductive methods. The study population included 20 technical officials, 1 Head of Public Procurement and 19 Contract Administrators. Data collection was conducted through interview, surveys and direct observation on the Public Procurement Portal. The results revealed areas of adequate compliance and critical aspects in the administrative management of contracts. The causes of non-completion of contracts on the Public Procurement Portal were mainly attributed to the change of Contract Administrators due to the departure of civil servants. Supervision by the Head of Public Procurement was determined to be average in relation to the publication of information in the contractual phase. As recommendations, it was suggested to evaluate and optimise administrative processes in the formalisation of contracts, develop a succession plan to mitigate the impacts of frequent change of Contract Administrators, provide continuous training and implement specific tools for the supervision of Contract Administrators.